Addressing Values in Co-Design Projects: Lessons Learned From Two Case Studies in Sensitive Contexts. Issue 1 (5th September 2022) - Ahmadi, Michael; Taugerbeck, Sebastian; Meurer, Johanna; Randall, Dave; Wulf, Volker
Abstract: Human–computer interaction (HCI) scholars and others have advocated treating design as inevitably implicating political and ethical sensitivities. A subset of those considerations has been the attempt to deal with the often conflicting interests of stakeholders through 'value sensitivity'. Drawing on value-sensitive design (VSD) as an inspiration, we emphasize the necessary way in which the evolving contextuality of the values in question shaped our research collaborations. This paper presents a retrospective analysis of two case studies from long-term user-centered design projects in fields with explicit ambitions for value-driven HCI research and concerned with emancipation and empowerment. The first, a 3-year project, entailed an explicit commitment to feminist policy initiatives with female participants that aimed at fostering values of gender equality. The second, a 4-year project, dealt with HCI research with and for older adults, where a multimodal mobility platform for ridesharing and public transportation was developed. We show how we translated general commitment into pragmatic, co-design research goals and infrastructures. The long-term ambition of our endeavors and integration of a broad stakeholder base were vital to support this. We additionally provide insights into how our approach offered safe spaces for trustful collaboration and flexibility when adapting methods to specific contexts.